Factors related to students achievement index of accounting department at Politeknik Negeri Samarinda-Indonesia - Hasiara, La Ode; Surya, Martin; Mersa, Nyoria Anggraeni (MEC-J (Management and Economics Journal), 2018)
This research purpose is to know and analyze the direct and indirect relationship between pedagogic competence, professional competence, social competence, personality competence, and service competence with student achievement index of Accounting Department at Politeknik Negeri Samarinda-Indonesia. This research uses quantitative approach by using Part Least Quare (PLS) model, with SPSS tool version for Windows 20. This study found a direct and indirect relationship between pedagogic competence, professional competence, social competence, personality competence, and service competence with student achievement index of Accounting Department at Politeknik Negeri Samarinda-Indonesia. It can be concluded that professional competence has a positive and significant effect on campus services provided to students of Accounting Department at Politeknik Negeri Samarinda-Indonesia. Similarly, campus service to students can give a positive and significant effect on index student achievement of Accounting Department at Politeknik Negeri Samarinda-Indonesia. The higher level of campus service can increase of student achievement index directly. It includes competence, professional; personality competence have significant indirect effect on student achievement index of Accountancy students in Politeknik Negeri Samarinda-Indonesia.Keywords: competence, service, student achievement index.